Additional Education for Children with Special Needs and Disabilities in the Russian Federation: National Monitoring Concept - Z. V. Puzanova; M. A. Simonova; V. M. Filippov; T. I. Larina (Moscow Polytechnic University, 2021)
The development of inclusive education progresses at different speeds across the world. In the Russian Federation inclusive education is developing primarily at the school level but one of the most crucial aspects of socialization is additional education, and in this regard the needs of children with special needs and disabilities remain an outstanding issue. A concept of the national monitoring of additional education for children with special needs and disabilities is proposed. The article presents the project of the toolkit for the national monitoring of entities engaged in additional educational activities for children with special needs and disabilities, which includes eight blocks: organizational structure of entities engaged in implementing additional educational programs for children in each constituent territory of the Russian Federation; implementation of additional educational programs for children with special needs and disabilities in entities with various subordination and organizational structures; material and technical support; staffing and professional training for specialists engaged in implementing additional educational programs for children with special needs and disabilities; information on ongoing additional educational programs for children with special needs and disabilities; typical obstacles which arise in the course of activities organized by entities engaged in implementing additional educational programs for children with special needs and disabilities; information resources and the system of inter-agency interaction in the course of the implementation of additional educational programs for children, including those with special needs and disabilities; financing of entities engaged in implementing additional educational programs for children. The presence/absence of a regional centre of additional education for children is going to be identified, as well as its official name, and the number of subordinate entities which implement additional educational programs in the corresponding Russian region in various areas: arts, sports, science, sociology and pedagogy, technical sciences, tourism and local history, intellectual games. The article could be of assistance for experts who study inclusion problems.